2015
DOI: 10.1097/bpo.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Anterior Instability of the Pediatric Shoulder

Abstract: Level III-retrospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 22 publications
2
20
0
1
Order By: Relevance
“…The negative influence of recurrent shoulder instability on the functional status of the shoulder and quality of life was not reported in previous studies. 3,17,21 Return to level of work and return to level of sports rates were similar to or higher than scores found in other studies. 1,7,16 Prognostic factors…”
Section: Discussionsupporting
confidence: 80%
“…The negative influence of recurrent shoulder instability on the functional status of the shoulder and quality of life was not reported in previous studies. 3,17,21 Return to level of work and return to level of sports rates were similar to or higher than scores found in other studies. 1,7,16 Prognostic factors…”
Section: Discussionsupporting
confidence: 80%
“…Although the graft choice does not appear to affect long-term outcomes with respect to recurrent patellar instability, pain, and return to activity, there is a clear trend toward questioning the long-term survival of MPFLR in the adolescent patient, independent of graft selection. As with all stabilizing surgeries in this high-risk population (shoulder instability, anterior cruciate ligament reconstruction 2 , 13 ), time may be a significant player in driving the reporting of unsuccessful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite lower reported recurrent anterior instability with operative treatment, recurrence after primary stabilization surgery remains high in adolescents. Studies looking specifically at adolescent patients have shown recurrence after primary stabilization surgery to range from 17 to 51%, and rates for specific subpopulations, such as contact athletes or those with glenoid or bipolar bone loss, may be even higher [11][12][13][14][15][16]. Thus, identifying risk factors for failure of primary stabilization surgery is of vital importance to choose the appropriate primary procedure or, when needed, address sources of possible failure in revision surgery.…”
Section: Introductionmentioning
confidence: 99%